2002
DOI: 10.1093/jexbot/53.371.1223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two CTR‐like protein kinases in Rosa hybrida and their expression during flower senescence and in response to ethylene

Abstract: The expression of two CTR-gene homologues was investigated during flower senescence in two Rosa hybrida cultivars. A fragment of a gene for a protein kinase, termed RhCTR1 (GenBank Acc. No. AF271206), was amplified by PCR and used to isolate the corresponding full-length cDNA (Acc. No. AY032953) from a rose petal cDNA library. The protein RhCTR1 has 66% amino acid identity to Arabidopsis CTR1. A fragment of a second CTR homologue, termed RhCTR2 (Acc. No. AY029067) is 69% identical to the corresponding region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…RhEIN3, a positive regulator of ethylene signaling was also constitutively expressed throughout the process under the influence of both exogenous ethylene and ABA. 121,122 Constitutive expression of Rh-EIN3-1 and Rh-EIN3-2 in cut rose is consistent with previous reports in Arabidopsis, 69 tomato, 123 or miniature potted roses, 124 where the expression of EIN3 remain unchanged even on being exposed to ethylene. A step further, Muller et al (2000a) 125 demonstrated the cultivar difference in ethylene receptor levels during flower development.…”
Section: -108supporting
confidence: 90%
“…RhEIN3, a positive regulator of ethylene signaling was also constitutively expressed throughout the process under the influence of both exogenous ethylene and ABA. 121,122 Constitutive expression of Rh-EIN3-1 and Rh-EIN3-2 in cut rose is consistent with previous reports in Arabidopsis, 69 tomato, 123 or miniature potted roses, 124 where the expression of EIN3 remain unchanged even on being exposed to ethylene. A step further, Muller et al (2000a) 125 demonstrated the cultivar difference in ethylene receptor levels during flower development.…”
Section: -108supporting
confidence: 90%
“…AR494803), the only complete CTR1-like protein so far described in species of the family Cucurbitaceae ( Table 2). The CpCTR1 and CpCTR2 proteins also share 61 and 62% identity with Arabidopsis CTR1 , and between 57 and 64% identity with CTR-like regulators in tomato (Leclercq et al 2002), Prunus persica (DalCin et al 2005), Rosa hybrida (Müller et al 2002), Malus 9 domestica (Wiersma et al 2007), Delphinium (Kuroda et al 2004) and Oryza sativa (Acc No. AK287946).…”
Section: Predicted Structural Features Of the Cpctr1 And Cpctr2 Proteinsmentioning
confidence: 99%
“…The CTR1 gene is unique in the genome of Arabidopsis ), but in tomato it has been identified as a multigenic family of four CTRlike genes (LeCTR1, LeCTR2, LeCTR3 and LeCTR4; Lin et al 1998Lin et al , 2008Leclercq et al 2002;Adams-Phillips et al 2004), and each of the genes appears to be involved in different tissues and processes. Two CTR-like genes have also been identified in Rosa hybrida (Müller et al 2002) and Actinidia deliciosa (Yin et al 2008). In the genome of other species such as Delphinium (Kuroda et al 2004), Malus 9 domestica (Wiersma et al 2007), Pyrus communis (El-Sharkawy et al 2003) and Prunus salicina (El-Sharkawy et al 2007), the CTR1-like gene appears to be unique as in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C may accumulate at high concentration in photosynthetic tissues, in which it is intimately in the regulation of photosynthesis and protect the chloroplasts against damage caused by ROS such as O 2 , H 2 O 2 , hydroxyl radicals (OH) and singlet oxygen [20]. The effect of non-enzymic antioxidants on the erythrocyte suspension was presented in Table 4.…”
Section: Effects Of Alkaloids On H 2 O 2 Induced Lipid Peroxidationmentioning
confidence: 99%